KEKERASAN, KERAPUHAN DAN DAYA TERIMA KUKIS YANG DIBUAT DARI SUBSTITUSI TEPUNG BIJI MANGGA (Mangifera indica L.) - Pramudya Kurnia; Kurnia Shinta Zulfiyani (SAGU, 2022)
The basic ingredients of food will affect the physical quality, including texture. Mango seed flour is one of the ingredients that has a fairly high carbohydrate, which is 69.77% and has the potential to be processed into food products, such as cookies. The purpose of this study was to determine the texture of cookies, i.e. hardness and fracturability, as well as the acceptability of cookies made from mango seed flour substitution. Type of this research was an experiment with a completely randomized design and the percentage of mango seed flour substitution is 0%, 5%, 10%, 15%. Texture was tested using texture analyzer and acceptability was obtained from the assessment of 40 panelists. The hardness data were analyzed using the Kruskal Wallis test. The results showed that the p-value of the hardness parameter was 0.372 and the p-value was 0.472. The acceptability test data were analyzed using the Kruskal Wallis test followed by Duncan’s test with the result that the p value for all parameters (i.e. color, aroma, taste, texture and overall) were <0.05 so that the use of mango seed flour had significant effect on all parameters of preference. Substitution with 5% mango seed flour becomes the product that has no significant different from the use of 100% wheat flour.